2016
DOI: 10.1073/pnas.1524303113
|View full text |Cite
|
Sign up to set email alerts
|

p11 modulates L-DOPA therapeutic effects and dyskinesia via distinct cell types in experimental Parkinsonism

Abstract: The reduced movement repertoire of Parkinson's disease (PD) is mainly due to degeneration of nigrostriatal dopamine neurons. Restoration of dopamine transmission by levodopa (L-DOPA) relieves motor symptoms of PD but often causes disabling dyskinesias. Subchronic L-DOPA increases levels of adaptor protein p11 (S100A10) in dopaminoceptive neurons of the striatum. Using experimental mouse models of Parkinsonism, we report here that global p11 knockout (KO) mice develop fewer jaw tremors in response to tacrine. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
(42 reference statements)
2
5
0
Order By: Relevance
“…Histological analyses confirmed that our transduction was limited to the dorsal striatum, and thus any motivational or behavioral consequences were unlikely to be related to off-target effects of p11. Our data are also consistent with the observation in our companion report (16), which demonstrated improvement in tacrine-induced tremor in transgenic global p11 Contralateral rotations were decreased in animals with inhibition of striatal p11 ipsilateral to the 6-OHDA lesions compared with lesioned mice receiving a control AAV after administration of apomorphine (B), L-dopa (C), D1R agonist SKF81297 (D), and D2R agonist quinpirole (E). ***P < 0.001, ****P < 0.0001, sh.p11 relative to sh.Luc controls, two-tailed t test.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Histological analyses confirmed that our transduction was limited to the dorsal striatum, and thus any motivational or behavioral consequences were unlikely to be related to off-target effects of p11. Our data are also consistent with the observation in our companion report (16), which demonstrated improvement in tacrine-induced tremor in transgenic global p11 Contralateral rotations were decreased in animals with inhibition of striatal p11 ipsilateral to the 6-OHDA lesions compared with lesioned mice receiving a control AAV after administration of apomorphine (B), L-dopa (C), D1R agonist SKF81297 (D), and D2R agonist quinpirole (E). ***P < 0.001, ****P < 0.0001, sh.p11 relative to sh.Luc controls, two-tailed t test.…”
Section: Discussionsupporting
confidence: 91%
“…This action also represents, to our knowledge, the first reported potential therapeutic benefit of inhibiting rather than increasing p11 activity, which is again consistent with the finding of reduced AIMs in total p11 KO mice reported in our companion paper (16). The companion study also reported reduced sensitization to rotational behaviors following L-dopa administration in lesioned p11 KO mice, but no difference compared with control mice at baseline.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, alterations of p11 or its binding partners are implicated in pathobiologies relevant to other diseases, including Parkinson’s disease (Zhang et al, 2008 ; Marongiu et al, 2016 ; Schintu et al, 2016 ; Green et al, 2017 ), drugs of abuse (Arango-Lievano et al, 2014 ; Thanos et al, 2016 ), and various cancers (Lokman et al, 2011 ; Lee et al, 2014 ; Noye et al, 2018 ; Bharadwaj et al, 2020 ; Lu et al, 2020 ), in which depression is a common comorbid condition. While the human Ahnak gene was initially cloned from tumor cells (Shtivelman and Bishop, 1993 ) and later characterized as a tumor suppressor (Lee et al, 2014 ), chemotherapy-induced p11/AnxA2/Supt6h complex is known to facilitate Oct4-mediated gene transcription and thereby is involved in chemotherapy-induced breast cancer stem cell enrichment (Lu et al, 2020 ).…”
Section: Outstanding Questionsmentioning
confidence: 99%
“…Postjunctional 5-HT1A receptors can strongly contribute to the mediation of the antidepressive effects of 5-HT (Artigas, 2015 ). It is of high interest that in these heteroreceptor complexes the receptor interacting proteins, like the scaffolding protein p11 (Svenningsson, 2014 ; Milosevic et al, 2017 ; Schintu et al, 2016 ), appear to play a substantial role (Fuxe and Borroto-Escuela, 2016 ). In human suicide victims reductions of p11 mRNA were established in hippocampus and amygdala and antidepressants enhance the expression of p11 in limbic regions of rodents (Svenningsson et al, 2013 ).…”
Section: Dysfunction Of the Gpcr Heteroreceptor Complexes Can Lead Tomentioning
confidence: 99%